STRATEGI DAKWAH MUI (MAJELIS ULAMA INDONESIA) JAWA TENGAH MELALUI SERTIFIKASI HALAL - Asri Wahyuningrum; H. Anasom; Thohir Yuli Kusmanto (Jurnal Ilmu Dakwah, 2015)
Halal product is part of responsibility muslims consumer by industrial. Halal product assurance based on majesty, who society have the right informations, clearly, and completely. This research aim is determine the certification of halal as a da’wa strategies of MUI Central Java and also supporting and inhibiting factors there. This Research used qualitative research using management of da’wa approach. The data were collected through techniques: interview, observation, and documentation. The data analysis are data: reduction, verification, and conclusion. The result of this research: there are two da’wa strategies used LPPOM MUI which on program Gerakan Masyarakat Sadar Halal "GEMAR HALAL", that became a certificationstrategy and the socialization and promotion strategies. The supporting factors are the availability of facilities and infrastructure, the cooperation of internal and external institution, the participation of community on the program, and members who competence and experience on their fields. Whereas inhibiting factors are some members who have double positions on one institution, lack of funds, and member’s lack of discipline on their work.***Memproduksi produk halal adalah bagian dari tanggungjawab perusahaan kepada konsumen muslim. Pada dasarnya keberadaan jaminan produk halal berangkat dari pertimbangan konsep luhur, bahwa masyarakat berhak mendapatkan informasi yang benar, jelas dan lengkap baik secara kuantitas maupun kualitas dari produk yang mereka konsumsi. Penelitian ini bertujuan untuk mengetahui sertifikasi halal sebagai strategi dakwah MUI Jawa Tengah serta faktor pendukung dan penghambatnya. Peneliti menggunakan penelitian kualitatif dengan pendekatan manajemen dakwah. Teknik pengumpulan datanya melalui wawancara, observasi, dan dokumentasi. Teknik analisis datanya yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa: ada dua strategi dakwah yang digunakan LPPOM MUI yang terdapat dalam program Gerakan Masyarakat Sadar Halal “Gemar HALAL”, yaitu strategi pensertifikasian dan strategi sosialisasi dan promosi.